2017
DOI: 10.1155/2017/4697194
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following Serial Intragastric Balloon Therapy for Obesity and Nonalcoholic Fatty Liver Disease in a Single Centre

Abstract: Background The incidence of nonalcoholic fatty liver disease (NAFLD) continues to parallel the rise in obesity rates. Endobariatric devices such as the intragastric balloon (IGB) may provide an alternative treatment option. Methods Outcomes following IGB treatment in 135 patients with obesity and NAFLD (mean baseline weight 117.9 kg; BMI 41.7 kg/m2; HOMA-IR 3.6) were retrospectively examined. Clinical, anthropometric, and biochemical changes were analysed at six months and after consecutive treatment with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…But also other endobariatric procedures like space-occupying devices, aspiration therapy and endoscopic small bowel bypass therapies have been proven to be successful in inducing weight loss (89,90). A single-centre retrospective cohort study following 135 patients with obesity and NAFLD undergoing intragastric balloon (IGB) treatment revealed changes in BMI after 6 months, as well as corresponding improvement of ALT, GGT and insulin resistance (HOMA-IR) scores (91). However, as endobariatric interventions are often temporary or less durable than bariatric surgery, aggressive weight maintenance afterwards is key for lasting weight reduction.…”
Section: Bariatric Surgery and Endobariatric Proceduresmentioning
confidence: 99%
“…But also other endobariatric procedures like space-occupying devices, aspiration therapy and endoscopic small bowel bypass therapies have been proven to be successful in inducing weight loss (89,90). A single-centre retrospective cohort study following 135 patients with obesity and NAFLD undergoing intragastric balloon (IGB) treatment revealed changes in BMI after 6 months, as well as corresponding improvement of ALT, GGT and insulin resistance (HOMA-IR) scores (91). However, as endobariatric interventions are often temporary or less durable than bariatric surgery, aggressive weight maintenance afterwards is key for lasting weight reduction.…”
Section: Bariatric Surgery and Endobariatric Proceduresmentioning
confidence: 99%
“…The main features of the studies of IGBs in NAFLD patients are shown in Table 2. Most of them assessed non‐invasive parameters of NAFLD such as liver steatosis measure by CT‐scan, 17 ultrasonography 18 or magnetic resonance imaging 19,20 . So far, only the small RCT by Lee et al have assessed changes in liver histology and showed a significant reduction of the NAFLD activity score after 6 months from Orbera™ placement 21 .…”
Section: Intragastric Balloonsmentioning
confidence: 99%
“…Gastric EBMTs have shown weight loss dependent improvement in histologic and biochemical parameters of NAFLD. [7][8][9][10] The proximal small intestine plays a central role in the pathogenesis of type II diabetes and NAFLD orchestrated through a variety of pathways, resulting in insulin resistance and chronic inflammation. These pathways include alteration of gut incretin to anti-incretin neurohormonal signaling, changes in the gut microbiome and mucosal barrier function, and activation of innate immune reactions caused by an excess of free fatty acids, bacterial lipopolysaccharides, chemokines, cytokines, and adipokines.…”
Section: Gastric Pathways Small Intestinal Pathwaysmentioning
confidence: 99%